Restless Legs Syndrome/Willis-Ekbom Disease in Multiple Sclerosis Patients with Spinal Cord Lesions - (:unkn) unknown (TURKISH NEUROPSYCHIATRY ASSOC-TURK NOROPSIKIYATRI DERNEGI, 2019)
Introduction: Spinal cord lesions in Multiple Sclerosis (MS) patients are associated with a higher risk of restless legs syndrome (RLS). In this study, we investigated the prevalence of RLS, sleep quality, presence and severity of depression, and the relationship of these parameters with cervical cord lesions in patients with RRMS. Methods: This study was conducted in the outpatient multiple sclerosis clinic of Marmara University Hospital between October 2013 - February 2014, including 93 patients with the diagnosis of MS. After signing informed consent, demographic data, comorbidities and actual medication of the patients were collected. All patients completed the surveys including Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS) and Beck Depression Inventory (BDI). Prevalence of HBS, sleep quality and depression severity were compared between those with and without cervical cord lesions. Furthermore, the relationship between RLS and sleep quality, depression and expanded disability status scale (EDSS) was assessed. Results: From overall patients, 72% were women (n=67) and 28% (n=26) were men. From all subjects, 32% (n=30) fulfilled IRLSSG diagnostic criteria. Fifty-seven percent of the patients (n=53) had pathological spinal cord lesions. Patients with RLS had significantly higher prevalence of pathological spinal cord lesions compared to patients without RLS (p=0.04). Sleep quality was found to be poor in both patients with cervical cord lesions and patients with RLS and this was statistically significant (p=0.031, p=0.0001). Conclusions: In summary, the possibility of RLS development in RRMS patients increases with the presence of lesions in spinal cord. Sleep quality was found to be poor in both patients with cervical cord lesions and patients with RLS. As RLS is a potentially treatable condition, increased awareness of diagnosis of RLS in MS patients may be important for early treatment and improve the comfort of the patient.YYYY
Keywords: Restless leg syndrome/Willis-Ekbom disease; multiple sclerosis; spinal cord lesions; PREVALENCE; SLEEP; POPULATION; FREQUENCY; MODEL